(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article discusses the goals and objectives of teaching mathematics in general secondary schools, modern methods, as well as the current problems in this area. The article also discusses the various objectives of teaching mathematics and ways to improve their mathematical literacy as a student.